Efektivitas Program Perumahan Bersubsidi Pada Produk KPR BTN Sejahtera iB (Studi Kasus: Bank Tabungan Negara Kantor Cabang Syariah Bekasi) - Rahayu, Fuji; Rahmawati, Rafika (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
The purpose of this study was to determine â€œThe Effectiveness of the Subsidized Housing Programon KPR BTN Sejahtera IB Products (Case Study: Bank Tabungan Negara Bekasi Sharia BranchOffice)â€, this research includes field research (field research) with qualitative methods and supportedby library research (library research). ) relating to the effectiveness of the subsidized housing programon KPR BTN Sejahtera IB products. Data collection techniques for this study consisted of observation,interviews, and documentation. As well as data analysis techniques for this thesis research usingtechniques: data reduction, data presentation and drawing conclusions. Measurement of effectiveness,seen from three factors, namely: first, convenience, second, target accuracy, and third, affordability.Based on the results of the research, it shows the effectiveness of the subsidized KPR program, namelythe convenience factor because the requirements, processes, forms of service, and administrative costshave been effective and affordable because it is easy for the public to obtain information about KPRBTN Sejahtera IB at Bank Tabungan Negara Bekasi Sharia Branch Office, monthly installments. ,details and total costs during the contract that are not burdensome, payment facilities have helpedcustomers, and there are no sanctions or fines if they experience arrears in payments every month,while the ineffectiveness is seen in the factor of the accuracy of targeting because many customerswho take the subsidized housing program are not occupied but only for investment. Therefore, it mustbe improved in all its aspects in order to produce optimal effectiveness for the subsidized housingprogram on the KPR BTN Sejahtera IB product at the Bekasi Sharia Branch Office State Savings Bank.